2021
DOI: 10.1002/eat.23570
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid mental disorders during long‐term course in a nationwide cohort of patients with anorexia nervosa

Abstract: Objective Comorbid mental disorders in anorexia nervosa during long‐term course require detailed studies. Method This matched cohort study was based on nationwide Danish register data of all patients born 1961–2008 with a first‐time ICD‐10 diagnosis of anorexia nervosa (AN) between 1994 and 2018 at age 8–32 and matched controls taken from all individuals without an eating disorder (ED). For nine categories of non‐eating mental disorders, time from date of first AN‐diagnosis (inclusion date) to time of first di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
3
21
0
2
Order By: Relevance
“…The baseline scores in the present population confirmed that depression and anxiety are among the most common comorbidities in AN [ 27 ]. Of noticeable importance, the improvement in depression scores during the hospitalization was not amplified by the pre-established pharmacologic treatment, which further underscores that inpatient treatment in itself reduces symptoms associated with AN.…”
Section: Discussionsupporting
confidence: 76%
“…The baseline scores in the present population confirmed that depression and anxiety are among the most common comorbidities in AN [ 27 ]. Of noticeable importance, the improvement in depression scores during the hospitalization was not amplified by the pre-established pharmacologic treatment, which further underscores that inpatient treatment in itself reduces symptoms associated with AN.…”
Section: Discussionsupporting
confidence: 76%
“…Patient were hospitalized due to moderate to severe AN, which was reflected in the high scores on all four EDE-Q subscales and total EDI score [20]. Current literature suggests that a significant portion of the individuals with AN suffer from additional psychiatric disorders or comorbidities with depression and anxiety being the most prevalent of all [27][28][29][30]. Indeed, the baseline scores of depression and anxiety with SCL-92 and MDI indicated moderate to severe depression, whereas the low scores in AQ ruled out that autism spectrum disorders would have impacted the results.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some people with AN have co-occurring psychopathologies that manifest in emotional vulnerabilities, including mood and anxiety disorders (Steinhausen et al, 2021), and emotion dysregulation (Haynos & Fruzzetti, 2011), which have been linked to excessive exercise (Peñas-Lled o, Vaz Leal, & Waller, 2002). Thus, they may engage in pathological exercise to cope with aversive affective state(s).…”
Section: Pathway 2 (Emotionally Vulnerable)mentioning
confidence: 99%